Socio-Demographic and Lifestyle Factors Influencing Adherence to AntiHypertensive Treatment in a Rural Area of Ludhiana, India - Sangeeta Girdhar; ,Mahesh Satija; Daljit Kaur; .Anurag Chaudhary (Global Journal of Medicine and Public Health)
Background